Relations Between Perceived Parental Acceptance and Children's Psychological Adjustment in the Context of Differential Parental Power and Prestige in Bangladesh. (August 2014) - Uddin, Muhammad Kamal; Khaleque, Abdul; Aktar, Rumana; Hossain, Kazi Nur
This article explored the effects of perceived maternal and paternal acceptance, power, and prestige on children's psychological adjustment. The sample consisted of 254 children (59% boys) ages 9 through 12 years ( M = 10.88) from Bangladesh. The measures used were the child versions of the Parental Acceptance–Rejection Questionnaire for mothers and fathers, the youth version of the Parental Power–Prestige Questionnaire, and the child version of the Personality Assessment Questionnaire. Results showed that perceived maternal and paternal acceptance were significantly correlated with children's (both boys' and girls') psychological adjustment. However, neither power nor prestige was significantly correlated with either maternal or paternal acceptance, or with children's psychological adjustment. Results of hierarchical regression analyses revealed that both perceived maternal and paternal acceptance made significant independent contributions to children's psychological adjustment. In addition, perceived maternal (but not paternal) power significantly moderated the relation between perceived maternal acceptance and children's psychological adjustment.